Accumulation of copper and zinc fractions in vineyard soil in the mid-western region of Santa Catarina, Brazil - da Rosa Couto R. (2015)
© 2014, Springer-Verlag Berlin Heidelberg.The application of fungicides to grapevines can cause the accumulation of Cu and Zn fractions in soil and increase their bioavailability and toxicity for plants. This study evaluated the accumulation and distribution of Cu and Zn fractions in the soil profile of a vineyard. In January 2012, stratified samples were collected from a 95-year-old vineyard and from a forest, which was used as a reference. The soil was dried, ground, and subjected to an analysis of chemical properties and chemical fractionation of Cu and Zn. Cu and Zn accumulated in the most superficial soil layers of the control area and vineyards; greater amounts were found in the soil of vineyards with more than 90 years of Bordeaux mixture application. Most of the Cu and Zn in the control area and vineyard soils were distributed in the residual fraction, with low geochemical mobility; however, they were also found in the most superficial layers of the vineyard soil. There were increases in the contents of soluble Cu, exchangeable Cu, and Cu bond to organic matter of the vineyard soil, especially in the most superficial layer of the soil. Most of the Zn in the vineyard soil was distributed in the residual fraction and bound to minerals, with low mobility but potential toxicity to plants.